The Albanian National Awakening - Skendi, Stavro (Book collections on Project MUSE., 2015)
Professor Skendi, a native of Albania, traces the progress and setbacks of Albania's long struggle for national unity during this least-known period of its intricate history. He discusses the heritage of its people and examines in detail the developments that led to Albanian independence: national resistance to the decisions of the Congress of Berlin, later opposition to Turkey, and the struggle between the Albanians and the Young Turks. Consideration is given to such internal problems as geographic configuration, religious and political division, and to such external problems as Italo-Austrian rivalry, political interference from neighboring states, and the involvement of great powers.Originally published in 1967.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.